Use of AFLPs to detect and measure variation in fungal populations - Majer, D.; Lewis, B.; Devos, P.; Mithen, R.; Oliver, Richard (1996)
A new PCR-based technique for the detection of inter- and intraspecific genetic variation has been tested on isolates of the fungal phytopathogens Cladosporium fulvum and Pyrenopeziza brassicae. The method is based on the selective PCR amplification of restriction fragments from digests of genomic DNA. We show that the technique is very efficient at detecting polymorphisms, even in species where very little variation could previously be found by RFLP analysis. 21 primer combinations were used on four isolates of P. brassicae, detecting a total of 162 polymorphisms (mean = 4·1 polymorphisms per primer combination per pair of isolates). Four primer combinations were used on eight isolates of C. fulvum, detecting a total of 32 polymorphisms (mean = 3·3 polymorphisms per primer combination per pair of isolates). Primer combinations varied in their ability to detect variation, ranging from 0 to 24 polymorphisms between P. brassicae isolates and 0 to 10 polymorphisms between C. fulvum isolates. AFLP fingerprints were highly reproducible and have great potential as a tool for evaluating genetic diversity of fungal pathogens